Herbal Recipes used by traditional healers towards Reproductive and Urinary healthcare in Wayanad (Kerala) India. - EK Dilipkumar; GR Janardhana; M. Abhijith (International Journal of Phytomedicine, 2017)
The traditional healers in Wayanad (Kerala), India possess rich aboriginal herbal medicinal knowledge (AHMK). This investigation has brought in to light many valuable therapeutic measures which were at the verge of extinction. Validation and documentation of some of such valuable in formation was hence done in order to conserve at least a part of this aboriginal ethno medicinal heritage. The study consists of three consecutive phases. In the first phase a methodology for the study including work plan was elucidated. A field level testing of the method was executed at a selected study site. In the second phase an extensive data collection cum field appraisal long three calendar years commences from July 2010 to July 2013 was conducted. In the final and third phase, validation and recording of the valid responses was done. A total of 60 species distributed in 56 genera belong to 38 families were identified being used in 67 recipes meant for 15 reproductive and urinary healthcare measures in Wayanad (Kerala), India. 31 herbs, 28 trees, 22 climbers and 16 shrubs were among the medicinal constituents. The therapeutic ingredients includes Fresh whole plants (12), dried whole plant (08), fresh root (2), dry root (29), fresh tuber (01), dried tuber (17), fresh bark (01), dried bark (02), fresh leaves (04) dried leaf (01), dried stem (01), dried petiole (01), pith powder (01), dried gum (2), fresh inflorescence (01), dried inflorescence (01), fresh flower (03), dried stamen (01), dried fruits (07), dried seeds (11), and seed oil (01). Validity stands maximum when FPVS was four and minimum when FPVS was two. Among the 67 medicinal recipes 59 has highest FPVS and the remaining 08 has mediocre FPVS. Many of the aboriginal herbal medicinal cultures (AHMC) and the associated therapeutic knowledge and practices still alive in the district are at the verge of extinction. The present study hence pivots around the conservation issues of this aboriginal medicinal heritage, particularly in the cure and management of urinary and reproductive ailments. This improves and sustains the aboriginal therapeutic system to contribute better to the national health repository.